Implementation of Integrated Learning to Enhance Elementary School Students' Creativity - Sofyan Iskandar; Primanita Sholihah Rosmana; Eldyana Citra Laksita; Tiominar Febrianti Puspita Sari; Wilda Nur Laila (Journal of Pedagogi, 2024)
In the field of education, which is constantly changing to innovate, implementing various methods in learning is important to strengthen students' understanding and creativity. Through integrated learning, students can gain direct experience, which enhances their ability to receive, retain, and apply learned concepts. This approach not only fosters a deeper comprehension of academic subjects but also encourages critical thinking and problem-solving skills. Furthermore, integrated learning helps students make meaningful connections between different disciplines, promoting a more holistic educational experience. This research is qualitative in nature, using a literature study approach, with books and literature as the main sources. By analyzing existing studies and theoretical frameworks, this research aims to identify effective strategies for integrating different subjects and activities in the classroom. This study is expected to contribute to the implementation of integrated learning to enhance creativity in elementary school students. Ultimately, the findings of this research could provide valuable insights for educators and policymakers, guiding them in developing curricula that better support student creativity and lifelong learning skills